Tindak Tutur Ilokusi Guru dalam Pembelajaran Bahasa Jawa Kelas VII di SMP Negeri 1 Yosowilangun - Oki Bagus Setiawan (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
This study aims to describe the analysis of teachers; illocutionary utterances in Javanese language learning at SMP Negeri 1 Yosowilangun. Research that focuses on the teacher speech using Javanese in schools that have a background in the Pandalungan community. This research is a qualitative research. The research method is using descriptive research. The source of the data was taken one of the Javanese language teachers who was on duty at SMP Negeri 1 Yosowilangun. Data collection used the tapping record technique during learning activities. Data analysis technique is by describing the utterances that has been transcribed in accordance with the pragmatic theory of illocutionary speech acts. The results showed that the analysis of teacher’s illocutionary speech acts in Javanese language learning were 5 illocutionary speech acts, namely; (1) illocutionary speech acts of assertive type, (2) directive, (3) commissive, (4) expressive, and (5) declarative and 4 functions of illocutionary speech acts namely; (1) competitive function, (2) convivial function, (3) collaborative function, and (4) conflictive function. Thus, Javanese language learning expressive speech acts with the intention of complaining and criticizing are most often used indirectly with the teacher.